Ethiopia’s Tree Seed and Forestry Systems: Challenges and Opportunities, and the Way Forward for Sustainable Seed Systems - Mohammed Adefa Seid (International Journal of Forestry Research)
Ethiopia’s tree seed and forestry sector is crucial for biodiversity conservation, climate change mitigation, and livelihoods. Yet it faces several challenges and opportunities. Challenges related to tree seed systems, including poor seed quality, limited access to genetically diverse seeds, and weak institutional frameworks, hinder reforestation and afforestation efforts. This review paper examines the current status of Ethiopia’s tree seed supply system, the role of formal and informal seed systems, and key constraints affecting seed availability and quality. The impacts of deforestation, land degradation, and climate change on seed production and forestry sustainability are also explored. Despite these challenges, opportunities exist to enhance Ethiopia’s tree seed systems through improved seed source management, community-based seed banking, policy reforms, and integration of indigenous knowledge with scientific advancements. Strengthening seed production and distribution mechanisms, along with research-driven strategies, is essential for sustainable forestry development in Ethiopia. Therefore, this review highlights the need for coordinated efforts among stakeholders to improve seed system resilience, ensuring the success of Ethiopia’s reforestation and landscape restoration initiatives.